Research on electric vehicle range under cold condition. (March 2022) - Zhao, Chen; Li, Yucheng; Yang, Yun; Wan, Song; Yu, Fuyong; Yu, Cheng; Deng, Chenghao; Zhou, Anjian; Shen, Xiaoyi
The effect of cold temperature on Electric Vehicle (EV) was investigated on an A class sedan through theoretical and experimental tests. Under cold weather, the drive range was reduced by 42.8% due to reasons such as the energy consumption of cabin heating, the reduction of electric energy capacity of battery and a reduction of efficiency of Electric Drive System (EDS). The cabin heating system is the biggest contributor for the reduction of drive range under cold temperature. Unlike the conventional vehicle where the engine waste heat is recycled, a Positive Temperature Coefficient (PTC) heater which directly withdraws electric energy from battery is used as the heat source for EV. This results in a reduction of EV range. Two approaches that can reduce the energy consumption of cabin heating system were investigated, namely the adoption of Intelligent Air Recirculation (IAR) and Heat Pump (HP). IAR and HP brought an increase of EV range under −7°C NEDC by 7.1%–7.9%, respectively. Another factor that causes range reduction is the deterioration of electric energy capacity of battery. To mitigate this adverse influence, research was conducted on two approaches: Motor Heat Recycle System (MHRS) and Active Motor Heat Control (AMHC). The adoption of MHRS system could improve the EV range by 7.9% while AMHC yielded an improvement of range by 2.1%. When the temperature decreases, the system efficiency of EDS decreases. One reason is the increase of oil splash loss as the oil viscosity increases under cold temperature. Hence, one type of oil with lower viscosity was tested and the results showed that the EDS efficiency could be improved by 1.5% which accounted for a 2.2% increase in driving range. With these measures implemented onto the test vehicle, the EV range under cold temperature −7°C NEDC could be improved by 26.5%.